Modern Trends and Developments in International Trade - Kovbatiuk Maryna V.; Shkliar Viktoriia V.; Kovbatiuk Heorhii О.; Pietukhov Andrii S. (Bìznes Inform, 2025)
The article provides an analytical overview of the structure and changes in international trade by technological product groups for the period 2000–2023. International trade is a significant driver of the global economy, and its structure is undergoing dynamic changes influenced by globalization, digitalization, regional integration, technological transformations, geopolitical factors, trade confrontations, pandemics, and military conflicts. It is determined that over the past two decades, global foreign trade turnover has significantly increased, especially after the COVID-19 pandemic. The study analyzes in detail the dynamics of exports and imports of products from various technological groups: primary products, raw materials, low-tech, medium-tech, and high-tech products. It has been revealed that the exports and imports of primary and raw materials are showing high growth rates in 2023, while high-tech products undergo uneven development due to global economic fluctuations, restructuring of supply chains, and technological constraints. Special attention is paid to structural changes, namely: the increase in the share of raw materials in global trade and the relative stability of the medium-tech sector. A decline in the share of low-tech goods has been recorded, indicating a gradual modernization of the global economy and a shift in demand. The analysis shows that stable demand for machinery and manufacturing products ensures the resilience of medium-tech industries in international trade. The results of the study demonstrate that analytical monitoring of the dynamics and structure of trade in technological products is crucial for shaping State policy, supporting national competitiveness, developing economic security strategies, and adapting businesses to changes in global market conjuncture. A deeper understanding of these processes allows for the identification of new opportunities for integration into global markets and ensuring sustainable economic development.